A Guardian of the UN Charter: The UN Secretary-General at Seventy-Five. Issue 3 (2020) - Ravndal, Ellen J.
Abstract: Over the past seventy-five years, the UN secretary-general has come to occupy a highly visible position in world politics. While the UN Charter describes the post merely as the "chief administrative officer" of the organization, today it is widely recognized that the secretary-general also plays a central role in political matters. What makes the role of the UN secretary-general special? Where does the office's authority come from? As part of the special issue on "The United Nations at Seventy-Five: Looking Back to Look Forward, " this essay looks back at the tenures of previous UN secretaries-general and applies ideas from sociological institutionalism to argue that the UN secretary-general holds the position of a "guardian" of the UN Charter. The UN secretary-general, more than anyone else within the UN system, represents the UN overall. From this flows great responsibilities and challenges, as the UN secretary-general is often expected to step in when other parts of the UN are unable or unwilling to act, and to take the blame when things go wrong. But this special position also endows the office with a substantial degree of authority, which future holders of the office can use to shape policies and mobilize support as the UN seeks to address urgent global challenges.